(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To present our experience in the examination and treatment of patients with peripheral exudative hemorrhagic chorioretinopathy (PEHCR). Material and Methods: We retrospectively reviewed the medical records of patients who were finally clinically diagnosed with PEHCR in the 2022-2023 period. History was collected and patients underwent ophthalmological examination including visual acuity, slit-lamp biomicroscopy, color fundus photography, fluorescein angiography and ocular ultrasound. All patients were treated with intravitreal anti-vascular endothelial growth factor (VEGF) therapy. One patient underwent vitreoretinal surgery. Results: PEHCR was diagnosed in 11 patients (13 eyes), including two patients diagnosed with bilateral lesions. Clinical signs identified included a dome-shaped hemorrhagic detachment of the peripheral retinal pigment epithelium (RPE) with massive exudations. One patient underwent vitreoretinal surgery for vitreoretinal hemorrhage. On B-scan ultrasonography, the PEHCR lesion commonly presented as a dome or plateau-shaped mass with hollow or solid acoustic quality. Ten patients were treated with intravitreal aflibercept. Conclusion: PEHCR is a chronic disease commonly associated with AMD. Detachment of the peripheral RPE is a major clinical manifestation of the disease, and may be complicated by sub-RPE hemorrhage in early disease. Anti-VEGF therapy is a major method of treatment whereas vitreoretinal surgery is indicated in complications accompanied by massive intravitreal hemorrhage or macula-threatening subretinal hemorrhage. Further investigation is needed to elucidate the etiology and pathogenesis of this entity and demonstrate the efficacy and safety of the aforementioned treatment modalities for PEHCR.